تحليل ترجمة رواية الإنجليزية "The Woman in White” لويلكي كولينز إلى اللغة العربية ذات الرداء الأبيض لمنة الله إبراهيم / The Analysis of the Arabic Translation of Wilkie Collins’s The Woman in White (Dhat al-Rida’ al-Abyad) by Mennatallah Ibrahim - Ma'Ahad Bin Mokhtar; Nuurul Malihah Binti Ahmed Kamel, (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2025)
ملخّص البحث: تهدف هذه الدراسة إلى تقييم ترجمة رواية The Woman in White من الإنجليزية إلى العربية في ضوء نظرية فيناي وداربلنيت؛ وذلك عبر تحليل مقاطع مختارة تكشف أساليب الترجمة المباشرة وغير المباشرة، واعتمدت الدراسة على المنهج الوصفي والتحليلي لرصد الظواهر الترجمية، وتبيّن كيفية تعامل المترجم مع التحديات اللغوية والثقافية بين النص الأصلي والنص الهدف، وأظهرت النتائج أن المترجم وازن بين عدة أساليب ترجمية؛ فاستعمل الترجمة الحرفية في بعض المواضع؛ بينما لجأ في مواضع أخرى إلى الإبدال، والتطويع والتكافؤ، مراعياً الخصوصية الأسلوبية للعربية، وضمان نقل المعنى بدقة وسلاسة، وبرز أسلوب الإبدال بوصفه الأكثر حضوراً، يليه التطويع، مع وجود حالات للتكافؤ والمحاكاة؛ بينما غاب أسلوب الاقتراض والتصرف تماماً، ولوحظت أيضاً حالات لجمع أكثر من أسلوب في موضع واحد أو إدخال إضافات وحذف؛لتوضيح المعنى أو ضبطه وفق مقتضيات النص العربي، وتوصلت أيضاً إلى أن المترجم نجح إجمالاً في الحفاظ على التكافؤ الدلالي والجمالي مع النص الأصلي؛ غير أن بعض المواضع كشفت عن غياب الاتساق في اختيار الأسلوب الأنسب؛ ما يبرز الحاجة إلى وعي أعمق بأساليب فيناي وداربلنيت وتدريب المترجمين على توظيفها بمرونة أكبر، تضمن التوازن بين الدقة اللغوية والحس الأدبي، وأما المترجمة فللمحافظة على التكافؤ الدلالي والجمالي مع النص الأصلي؛ غير أنّ بعض المواضع أظهرت تبايناً في اختيار الأساليب الأنسب، وقد انعكس هذا التباين في عدد من المواضع داخل الترجمة. الكلمات المفتاحية: الترجمة الأدبية، فيناي وداربلنيت؛ الإبدال، التكافؤ، التحليل النصي. Abstract: This study aims to evaluate the translation of the novel The Woman in White from English into Arabic considering Vinay and Darbelnet’s theory. This is accomplished through the analysis of selected passages that illustrate both direct and indirect translation techniques. The study adopts a descriptive and analytical approach to examine translational phenomena and to show how the translator addressed the linguistic and cultural challenges between the source and target texts. The results indicate that the translator employed a balanced range of translation techniques. In some cases, literal translation was used, while in others, substitution, adaptation, or equivalence was applied, taking into consideration the stylistic features of Arabic and ensuring an accurate and fluent transfer of meaning. Substitution emerged as the most frequently used technique, followed by adaptation, with fewer instances of equivalence and imitation. Borrowing and adaptation were entirely absent. The study also identified cases in which multiple techniques were combined within a single passage, as well as instances of additions and deletions introduced to clarify or adjust meaning according to the requirements of the Arabic text. The study concludes that the translator largely succeeded in maintaining semantic and aesthetic equivalence with the original text. However, some instances revealed inconsistency in the choice of the most appropriate style, underscoring the need for a deeper understanding of Vinay and Darbelnet’s methods and for training translators to apply them with greater flexibility. Such an approach helps maintain a balance between linguistic accuracy and literary sensibility while preserving semantic and aesthetic fidelity to the source text. Nonetheless, some inconsistencies in stylistic choices were observed across several parts of the translation. Keywords: Literary translation, Vinay and Darbelnet, substitution; equivalence, textual analysis. Abstrak: Kajian ini bertujuan menilai terjemahan novel The Woman in White daripada bahasa Inggeris ke bahasa Arab berdasarkan Teori Vinay dan Darbelnet, melalui analisis petikan terpilih yang menonjolkan penggunaan strategi terjemahan langsung dan tidak langsung. Kajian ini menggunakan pendekatan deskriptif dan analitis bagi mengenal pasti fenomena penterjemahan serta menjelaskan cara penterjemah menangani cabaran linguistik dan budaya antara teks sumber dan teks sasaran. Dapatan kajian menunjukkan bahawa penterjemah mengimbangi pelbagai strategi terjemahan; terjemahan literal digunakan dalam beberapa konteks, manakala dalam konteks lain penterjemah menggunakan penggantian, penyesuaian dan kesepadanan, dengan mengambil kira ciri gaya bahasa Arab serta memastikan pemindahan makna yang tepat dan lancar. Strategi penggantian didapati paling dominan, diikuti oleh penyesuaian, manakala kesepadanan dan peniruan digunakan dalam kes-kes tertentu. Sebaliknya, strategi peminjaman dan transformasi bebas tidak digunakan sama sekali. Kajian ini juga mengenal pasti penggunaan gabungan lebih daripada satu strategi dalam satu konteks, selain penambahan dan pengguguran unsur tertentu bagi memperjelas atau menyesuaikan makna selaras dengan keperluan teks Arab. Kesimpulannya, penterjemah secara umum berjaya mengekalkan kesepadanan makna dan nilai estetika dengan teks asal. Namun begitu, beberapa bahagian menunjukkan ketidakkonsistenan dalam pemilihan strategi yang paling sesuai, sekali gus menonjolkan keperluan kepada pemahaman yang lebih mendalam terhadap pendekatan Vinay dan Darbelnet serta latihan penterjemah yang lebih sistematik dan fleksibel. Pendekatan sedemikian penting bagi memastikan keseimbangan antara ketepatan linguistik dan kepekaan sastera dalam terjemahan karya sastera. Kata kunci: terjemahan sastera, Vinay dan Darbelnet, penggantian, kesepadanan, analisis teks.